1998
DOI: 10.1111/j.1749-6632.1998.tb09026.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Emotional Response to Psychological Stressors in Psychiatric and Psychosomatic Disorders

Abstract: Deviations from emotional and physiological homeostasis in humans occur under episodic, chronic, or traumatic stress experiences. These dysregulations can provoke emotional and physical disturbances that may result in stress-related psychiatric or psychosomatic disorders. This brief review discusses a variety of both naturally occurring and experimental stressors and the complexity of intervening variables on cardiovascular and hormonal dysregulations of the hypothalamic-pituitary-adrenal (HPA) axis. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 84 publications
0
17
0
1
Order By: Relevance
“…The sympathetic-adrenomedullary systems in the brain and at the periphery are the fastest systems activated to induce the 'flightÏfright' response during the stage of alarm reaction. The magnitude of the effect of the systems has been evaluated by monitoring the sympathetic-adrenomedullary systems directly (adrenaline and NAd release) or studying psychophysiological measures (heart rate, blood pressure, and skin conductance responses) or physical and emotional well-being (Ehlert & Straub, 1998). In the chain of reactions by which the brain co-ordinates the stress response, the sympathetic-adrenomedullary systems constitute key components, with a dominant role for catecholamines as primary messengers in the flightÏfright response.…”
Section: Resultsmentioning
confidence: 99%
“…The sympathetic-adrenomedullary systems in the brain and at the periphery are the fastest systems activated to induce the 'flightÏfright' response during the stage of alarm reaction. The magnitude of the effect of the systems has been evaluated by monitoring the sympathetic-adrenomedullary systems directly (adrenaline and NAd release) or studying psychophysiological measures (heart rate, blood pressure, and skin conductance responses) or physical and emotional well-being (Ehlert & Straub, 1998). In the chain of reactions by which the brain co-ordinates the stress response, the sympathetic-adrenomedullary systems constitute key components, with a dominant role for catecholamines as primary messengers in the flightÏfright response.…”
Section: Resultsmentioning
confidence: 99%
“…3 D -amphetamine Induces Sensitization of HPA Axis 287 tant factor in the development of many forms of human disease (McEwen 2000;Koob and Le Moal 2001). A wealth of evidence suggests that an increased reactivity to stressors and/or the inability to respond effectively and appropriately to stressors plays an important role in the development and expression of many forms of mental illness (Ehlert and Straub 1998;Kreek and Koob 1998;Dohrenwend 2000;Heim et al 2000). Clearly, a better understanding of the underlying neurobiology of this sensitivity to stressors may help in the prophylaxis and treatment of these disorders.…”
Section: Previous Studies Have Demonstrated That Exposure To Psychostmentioning
confidence: 99%
“…In particular, responses of the hypothalamus-pituitaryadrenal (HPA) axis to stress have been widely investigated with contrasting results in healthy subjects and psychiatric patients: larger cortisol (CORT) responses to psychological stress were evidenced in male subjects than in females by Kirschbaum et al [6], while in another experimental evaluation, CORT was not increased by a psychological stressor, but was stimulated by physical stress in normal subjects [7]. Among adults, HPA axis dysregulation in coping reactions seems to be associated with psychosomatic disorders [8] and with posttraumatic stress disorder [9,10]. It has been suggested that hypersecretion of corticotropin-releasing factor (CRF) and HPA axis hyperactivity contribute to the symptomatology of anxiety-related disorders [11].…”
Section: Introductionmentioning
confidence: 99%